2019 IEEE Winter Conference on Applications of Computer Vision (WACV) 2019
DOI: 10.1109/wacv.2019.00061
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Painting to Natural Image: A New Solution for Painting Processing

Abstract: Collecting a large-scale and well-annotated dataset for image processing has become a common practice in computer vision. However, in the ancient painting area, this task is not practical as the number of paintings is limited and their style is greatly diverse. We, therefore, propose a novel solution for the problems that come with ancient painting processing. This is to use domain transfer to convert ancient paintings to photo-realistic natural images. By doing so, the "ancient painting processing problems" b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The Artistic-Faces dataset contains artistic portraits of 16 different artists and there are only 10 images per artist available. For the landscape, we use the CLP dataset [29] that contains thousands of landscape photos as the source and 10 pencil landscape drawings as the target. Evaluated methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Artistic-Faces dataset contains artistic portraits of 16 different artists and there are only 10 images per artist available. For the landscape, we use the CLP dataset [29] that contains thousands of landscape photos as the source and 10 pencil landscape drawings as the target. Evaluated methods.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore one conjecture is that the performance of the propose method will decrease when the source and target domain become more dissimilar. To validate this, we select the FFHQ [16] face dataset as the source domain and several target domains for adaptation according to their dissimilarity with FFHQ: the CelebA-Female face [24], the emoji face [11], the cat face [3], and the color pencil landscape [29].…”
Section: Discussionmentioning
confidence: 99%
“…In our task, we want to optimize the pixel-level matching of the label and output. Previous approaches have found that adding the MAE loss is beneficial to image restoration at the pixel level [44,45]. We use the MAE loss for less blurring in the estimated sinogram:Lsinofalse(Gfalse)=Ex~Pdatafalse(xfalse),z~Pzfalse(zfalse)[yGfalse(x,zfalse)1], where z is the noise, G(x,z) is the estimated sinogram, and x1 is the l1 norm of x.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research shows that mean absolute error (MAE) loss is commonly used in CycleGAN, which is conducive to pixel-level image approximation (35,44). Thus, the projection domain loss function is constructed based on the MAE loss, and it is expressed as:…”
Section: Projection Domain Lossmentioning
confidence: 99%